Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.6 - Other Types of Equations - 1.6 Exercises - Page 128: 54


-3, 1

Work Step by Step

$4/(x+1)-3/(x+2)=1$ 4(x+2)-3(x+1)=(x+1)(x+2) $x+5 = x^2+3x+2$ $x^2+2x-3 = x^2+3x-x-3=x(x+3)-1(x+3)=0$ $(x+3)(x-1)=0$, giving x=-3 or 1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.